Pengembangan Multimedia Interaktif Berbasis Articulate Storyline Pada Mata Pelajaran SBdP Materi Montase Kelas IV Sekolah Dasar - Lutfi Anwar Asrori; Rofian Rofian; Wawan Priyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine the characteristics of the interactive multimedia development based on Articulate Storyline in the subject of SBdP montage material and to determine the validity and practicality of interactive multimedia based on Articulate Storyline which was developed. This type of research is research and development or Research and Development (R&D). The procedure in this study uses the Borg and Gall research and development model until the 5th stage, namely research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision. Data was collected through observation, interviews, questionnaires, and documentation. The results of data analysis showed that the average results of the media expert validation questionnaire were 83.47% with the criteria of "very good", material validation 94.66%, with the criteria of "very good", the teacher's response 96% with the criteria of "very good", the response students 99.3%, with the criteria of "very good". The conclusion is that the interactive multimedia based on Articulate Storyline in the SBdP subject of montage material for grade IV elementary school is valid and practical to use in learning.